The effect of the exercise environment and the level of involvement on bone mineral health - Massini, Danilo A. [UNESP]; de Souza Martins, Nilson D. [UNESP]; de Oliveira, Thiago P. [UNESP]; Macedo, Anderson G. [UNESP]; Castro, Eliane A. [UNESP]; Almeida, Tiago A. F. [UNESP]; Santos, Fernando J.; Espada, Mário C.; Pessôa Filho, Dalton M. [UNESP] (Springer Nature, 2023)
Introduction: This study aimed to compare athletes practicing exercise in different environments with non-active young and elderly men and women regarding bone mineral density (BMD), hypothesizing that BMD values differ between athletes according to the environment of exercise practice, but those training in a low-gravitational environment have no different stimuli to BMD increasing if compared with healthy peers experiencing reduced exercise involvement, whatever the age group and sex. Materials and methods: 104 participants of both sexes were selected according to the environment of exercise practice [swimmers (N = 26) and judo fighters (N = 26)], and exercise level of involvement [non-active young (N = 26) and older adults (N = 26)]. Dual-energy X-ray absorptiometry provided BMD, lean mass, and fat mass (FM) for the whole body (WB), upper (UL), and lower limbs (LL). Results: For the BMD in WB, UL and LL no effects of group and sex were observed (p > 0.05). Post-hoc analyses detected higher values of BMD in UL for female swimmers compared to non-active older adults (p < 0.05), while judo fighters showed higher BMD in WB, UL, and LL than other participants whatever the sex (p < 0.01). Lower FM was observed for WB, UL, and LL when swimmers and judo fighters were compared to non-active young and older female peers (p < 0.01). Conclusion: The findings emphasized that BMD stimuli with swimming are reduced when compared to judo, and despite the stimuli in swimming is not distinguishable from that affecting BMD in WB, UL and LL of non-active young, it is effective in differing BMD in UL among non-active older for women.
Keywords: Bone density; Impact sport; Lean body mass; Sex; Swimming